Challenges in pulmonary fibrosis · 4: Smoking‐induced diffuse interstitial lung diseases - Wells, Athol U (BMJ Group, 2007)
Smoking‐induced diffuse interstitial lung processes include respiratory bronchiolitis, respiratory bronchiolitis‐associated interstitial lung disease (RBILD), desquamative interstitial pneumonia (DIP) and Langerhans' cell histiocytosis. The histological, radiological and clinical features of respiratory bronchiolitis, RBILD and DIP are reviewed, with particular reference to management issues; Langerhans' cell histiocytosis is covered elsewhere in this series of articles. Possible relationships between smoking and other diffuse lung diseases are explored briefly.